Peppermint Candy - Chang-dong, Lee; Kim Hyung-koo; Sul, Kyung-Goo; Kim Yeo-jin; Suh Jung (Third Window Films, 2010)
The bittersweet chronicle of twenty years in the life of one man, told in reverse. Although the premise could be written off as a simple gimmick, "Peppermint Candy" is a masterfully told tale of love and loss that invites repeat viewings. Sul Kyung-Gu is magnetic as the film's tragic protagonist. [www.lovehkfilm.com]
Keywords: DVD-Video